PENERAPAN METODE DEBAT AKTIF (ACTIVE DEBATE) PADA PEMBELAJARAN AL-QURAN HADIST DI MADRASAH - Al Wafi, Rafdi (Institut Syekh Abdul Halim Hasan Binjai, 2022)
Often we as educators who are new to feeling silence in class, so the class runs in monotone, therefore the author wants to apply one of the learning methods, namely the active debate method. The active debate method is a method that helps students channel their ideas, thoughts and opinions by asking questions. The approach used is a qualitative approach. By applying and developing active debate learning methods, students can improve their ability to ask and answer questions in participating in ongoing learning. The aim is to find out the steps for applying the active debate method to learning the Al-Qur'an Hadith in madrasas. Based on the discussion carried out, the application of active debate is carried out with the following steps, starting from preparing a question, dividing the class into two teams, preparing arguments, then starting the active debate method, then identifying the best arguments according to the students.